The Concept of Gynecologic Oncology Services in Jakarta Related to Academic Health System - Sigit Purbadi (Indonesian Journal of Obstetrics and Gynecology, 2017)
An Academic Health System (AHS) is a system in partnership among universities and health care providers that focuses on education, training, service, and research. The final outcome of this partnership is to improve health status. Numerous countries have been using this system, since this system is proven to lead to better sustainable outcome.The vision of Faculty of Medicine, University of Indonesia (FMUI) is "to create infinite experience for all through Academic Health System". The third mission of FMUI is to integrate the AHS to Dr. CiptoMangunkusumo Hospital and its other affiliated hospitals.The division of Oncology Department of Obstetrics and Gynecology is a part of Academic Health System that is responsible to create the Gynecologic Oncology services in this system. We create the gynecologiconcology services in preventive approach from primary to tertiary prevention.The sister hospitals of FMUI’s including Dr. Cipto Manungunkusumo, Persahabatan, Fatmawati, Karawang, and Tangerang General Hospital. Ideally, we should have health provider partners from primary, DistrictHospital (Rumah Sakit Umum Kecamatan/RSUK and Rumah Sakit Umum Daerah/RSUD). Another partner in collaborative project of AHS is Organization of Health Care Professions, such as Indonesian Medical Association, Indonesian Obstetrics and Gynecology Society, and Indonesian Gynecologic Oncology Society, and nongovernmental organization such as Female Cancer Program, Indonesian Cancer Foundation and others are part of partnership in AHS. When talking about public health status, it is also necessary to talk about the role of government as the policy maker and The Social Warranty Institution (Badan Penyelenggara Jaminan Sosial Kesehatan, BPJS) as the public health care insurance regulator. Primary health care should be included in the AHS’s partnership members because primary prevention strategy should be conducted in primary health care.The example of this project is Cervical Cancer Surveilance as a pilot project. We would prepare the project in collaborative meeting with all partners to make proposal in gynecologic oncology services in primary,secondary, and tertiary health care, and finally Dr. Cipto Mangunkusumo Hospital as the national referral Hospital. The proposal should talk about concepts of education, training, service, and research. Primary health care can promote cervical prevention and early detection via visual inspection using acetic acid and Pap test.Cervical precancer lesion can be treated using cryotherapy in primary health care. In secondary health care setting, cervical precancer lesion until microinvasive cervical cancer (stage 1A1) can be treated. Invasive cervical cancer should be managed in tertiary health care. We are preparing concepts where all services should follow the Clinical Practice Guideline. All medical patient database should be recorded digitally as long term cohort data. By applying this system, we’ll have a large number of patients’ data from primary to tertiary health care.This is crucial, considering that the process of education, training, and research of medical students, residents, and fellows is the backbone of AHS in improving health care status.